(3GdHQgGf aj hLhg GdHjGfs - (3bOGeI Hf LYaQ Hf bOGeI Hf RjGO GdHZOGOj, CHh GdaQL,J (B337 (3g` s
(3ChdgG (B:s
(3Ef Chdi eG GaJJM Hg GddHjH cJGHg hGHJOC Hg GdCOjH NWGHg eG GaJJM Gddg Hg YR hLd GdbQBf hLYdg BNQ OYhi dCgd GdEjeGf s
(3BNQgG (B:s
(3Je cJGH GdHQgGf ai hLhg GdHjGf hGdefI ddg hGdYRI ddg QH GdYGdejf s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B191 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B128s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GddZIs